Peningkatkan kemampuan menyusun kalimat menggunakan media video animasi pada peserta didik tunarungu kelas VII di SLB Negeri Boyolali - Feri Gilang Palupi; Avinda Fahirani; Shalsa Nida Hanifah; Priyono Priyono; Novi Noer Rahmawati (Universitas Sebelas Maret, 2025)
This research aims to improve the learning process and increase the ability to compose sentences through animated video media which focuses on the learning process in the classroom and increasing the ability to compose sentences for children with hearing impairments. This research is a classroom action (PTK) with the subject of children with hearing impairments in class VII SLB N Boyolali. The research was carried out in 2 cycles and data collection techniques used tests and observation. Data analysis techniques use qualitative and quantitative descriptive. The results of the research show that the ability to compose sentences using animated video media in class VII hearing impaired children has increased. This is proven by the increase in scores on test results. In the pre-action test, student G obtained a score of 60,00 in cycle 1 to 80,00 in cycle 2, increasing to 93,33. KL students in the pre-action test obtained a score of 53.33 in cycle 1 to 60.00 in cycle 2, increasing to 86.66. KH students in the pre-action test obtained a score of 46,66 in cycle 1 to 53,33 in cycle 2, increasing to 80,00. NR students in the pre-action test obtained a score of 53.33 in cycle 1 to 66.66 in cycle 2 to 86.66. Student NM in the pre-action test obtained a score of 33.33 in cycle 1 to 53.33 and in cycle 2 it increased to 66.66. Thus, it can be concluded that this research shows an increase in the ability to compose sentences through the use of animated video media in class VII hearing impaired children at SLB N Boyolali.